Síntese e caracterização da estrutura metal orgânica uio-66 superácida e sua aplicação em catálise para a produção de ésteres etílicos de ácidos graxos - Bento, Ivan Edimar (2022)
Facing the need of developing technologies for biofuels, this work has as general objective the synthesis of the structures and evaluation of the catalytic behavior of the Metal-Organic Structures (MOFs) UiO-66 in esterification/transesterification reactions of soybean degummed oil with ethyl alcohol. The development of the work consisted in the synthesis and characterization of the metal organic framework UiO-66 in original form and containing post-synthesis modifications for the increase of its surface acidity and the application of these materials in acid catalysis for the production of fatty acid ethyl esters. The synthesis of the metal organic UiO-66 structure was carried out via solvothermal and the post-synthesis acid modifications were performed by sulfation reactions. Three procedures were performed: heating to 150 °C and two sulfation processes in different concentrations of sulfuric acid containing solution. The materials were characterized by Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffractometry (XRD), X-ray Fluorescence (XRF), Nitrogen Adsorption/ Desorption (BET), Scanning Electron Microscopy (SEM-EDS) and Apparent Acidity (pH) analyses. The synthesis of UiO-66 obtained 86% yield with respect to the theoretical stoichiometry. Infrared spectroscopy provided information about the main characteristics of the chemical bonds between the organic part of terephthalic acid and the zirconia-containing cores. The XRD evaluation indicated the presence of signals characteristic of the UiO-66 structure, however, the addition of sulfuric acid in the sulfation step generated important crystalline modifications in its structure. The XRF analysis provided information about the metal oxides and sulfate ions present in the analyzed samples. Nitrogen Adsorption/ Desorption (BET) analysis found that the original UiO-66 structure has a specific area as described in the literature, which depending on the synthesis method can range from 800 to 1200 m2 g-1. The postsynthesis modifications reduced this specific area in the sulfated structures. Scanning Electron Microscopy (SEM-EDS) provided a visual evaluation of the main crystalline modifications and with the EDS technique coupled to the SEM it was possible to add with the (FRX) and (FTIR) analyses and observe the insertion of the sulfate ions in the modified structures. With the Apparent Acidity (pH) test it was found that, with the insertion of sulfate ions in the structure, the pH reduced its value and this behavior gave a higher acidity to the structure analyzed. After the characterization of the material and following an experimental planning 23 with face centered central compound, the esterification/transesterification reactions of the degummed soybean oil were performed, aiming to determine the best reaction conditions. With the help of statistical analysis the best performing catalyst and the best reaction conditions for the catalyst reuse study were determined, reaching ethyl ester yields up to 95% with the UiO-66-S35 structure and keeping the catalyst active for three cycles.